Character Building Through Exemplification and Habitual Practices at API ASRI Islamic Boarding School Tegalrejo Magelang - Hidayat, Wahyu; Nur Hidayat (Islamic Education Management Study Program, Faculty of Tarbiyah and Education State Islamic University (UIN) Sunan Kalijaga Yogyakarta, Indonesia, 2024)
Purpose – This study aimed to explore the development of student responsibility through the exemplification and habituation practices of teachers at Pondok Pesantren API Asri Tegalrejo Magelang. Design/methods– Employing a qualitative phenomenological approach, the study involved seventh-grade male students who are also residents of the boarding school. Data were collected through observations, interviews with key informants, and document analysis. The analysis followed Miles and Huberman's framework, focusing on data reduction, data display, and conclusion drawing/verification. Findings – The findings indicate that character formation is significantly influenced by consistent teacher-led initiatives, emphasizing communal practices, ethical discourse, and disciplined routines. These practices contribute to the holistic development of responsibility in students, reinforcing qualities such as ethical adherence, decision-making, initiative, adaptability, and cooperation. Research implications/limitations – The study highlights the importance of structured, habitual practices led by exemplary teachers in fostering student responsibility. Limitations include the unique boarding school environment and the need for adaptation in different educational contexts. Future research should explore the adaptability of these practices across diverse settings and their long-term impacts on student behavior. Practical implications – Educational institutions aiming to foster student responsibility should integrate structured, habitual practices led by exemplary teachers. This approach not only enhances character development but also emphasizes the importance of teacher training and development in ethical and responsible behavior. Originality/value – This study provides insights into the effective methods of character education in an Islamic boarding school context, demonstrating the critical role of teacher behavior and structured routines in developing student responsibility and ethical behavior.